The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/7908072
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Oxidative Damage and Involvement of Nrf2‐ARE Pathway in Mesodopaminergic System and Hippocampus of Status Epilepticus Rats Pretreated by Intranasal Pentoxifylline

Abstract: The current studies were aimed at evaluating the efficacy of intranasal pentoxifylline (Ptx) pretreatment in protecting mesodopaminergic system and hippocampus from oxidative damage of lithium-pilocarpine induced status epilepticus (SE) and the involvement of nuclear factor erythroid 2-related factor 2- (Nrf2-) antioxidant response elements pathway. Pentoxifylline was administered to rats intranasally or intraperitoneally 30 minutes before inducing SE. Our results showed the impaired visuospatial memory, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…The activated nerve/glial cells stimulate HMGB1‐TLR4 signalling, which triggers Ca 2+ release, resulting in increases neuronal excitotoxicity leading to frequent seizures, and precipitate to neuronal damage. Based on these mechanisms, HMGB1‐TLR4 network signalling plays a fundamental role in epileptic seizures initiation and progression 28,31 . The current data were matched with the previous studies, 2,30 which indicated the relationship between HMGB1‐TLR4 signalling pathway and epileptogenesis, since it revealed upregulated pro‐inflammatory cytokines, HMGB1 and TLR4, which hindered by PTX treatment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The activated nerve/glial cells stimulate HMGB1‐TLR4 signalling, which triggers Ca 2+ release, resulting in increases neuronal excitotoxicity leading to frequent seizures, and precipitate to neuronal damage. Based on these mechanisms, HMGB1‐TLR4 network signalling plays a fundamental role in epileptic seizures initiation and progression 28,31 . The current data were matched with the previous studies, 2,30 which indicated the relationship between HMGB1‐TLR4 signalling pathway and epileptogenesis, since it revealed upregulated pro‐inflammatory cytokines, HMGB1 and TLR4, which hindered by PTX treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Pentoxifylline is broadly utilized therapeutically to enhance the circulation in peripheral vascular diseases 26 . Several studies have reported PTX evoked repression in HMGB1 production with apparent reduction in its downstream inflammatory/oxidative networks, mediated by TLR4 leading to subsequent decreased oxidative stress and improved pathophysiological conditions in the chronic inflammatory diseases 17,18,27,28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentoxifylline (PTX), a methylxanthine derivative, has been applied clinically for the treatment of peripheral vascular diseases and cerebrovascular diseases [21]. Furthermore, it was reported that PTX has ameliorative effects on aging or other pathological processes, such as improving behavioral deficits and anti-inflammatory activity, restoring dopaminergic neurochemical levels and antioxidant activity, and ameliorating mitochondrial function [22][23][24][25]. These findings are also supported by our earlier research on the antiaging effects of PTX in aged rats, in which we found that the beneficial function might be related to Nrf2 activation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with intraperitoneal injection, IN pentoxifylline delivery completely restored the visuospatial memory and the activity of the mesodopaminergic system in status epilepticus rats. The findings obtained suggest that IN administration of pentoxifylline could effectively protect cells from oxidative damage in status epilepticus and may hopefully become a non-invasive, painless, and easily administered option for epileptic patients [62].…”
Section: Intranasal Administration To Reach the Brainmentioning
confidence: 99%